THE INFLUENCE OF DRYING SEEDLESS VARIETIES OF GRAPES BY DIFFERENT METHODS ON THE YIELD AND QUALITY OF THE FINISHED PRODUCT (Лучшие интеллектуальные исследования, 2025)
Abstract: In the course of studying the mechanical composition and organoleptic value of finished grape products from seedless grape varieties dried using various drying methods, research was conducted to determine the mass of 100 raisins, raisin size (length, width, mm), and tasting score (score) of raisin grape varieties grown in the Fergana region without sun drying (control).Annotation: During the study of the mechanical composition of grape products in the Fergana region, mainly 100 raisins, raisons ( raisions , ei , mm), tasting prices based on the mechanical composition of grape grape varieties in various methods (points), research has been held.Annotation: during the study of the mechanical composition of vineyard products in the Fergana region, in the main 100 varieties, Raisions ( Raisions , EI, MM), degustation prices based on the mechanical composition of grapevine varieties and different methods (tochki), research was carried out.